Changes in aquatic microbial responses to C-substrates with stream water and sediment quality related to land use pressures. (October 2017) - Stutter, Marc I.; Cains, Jonathan
Abstract: The degradation of aquatic ecosystems by multiply-acting stressors is a key threat requiring new approaches to identify impairment processes and restoration targets. Heterotrophic respiration of C-substrates can be an integrative indicator of how aquatic ecosystems respond to pollution. We utilised sixteen C-substrates (simple metabolites to dissolved organic matter (DOM)) to characterise substrate induced respiration (SIR) for sediments from sixteen NE Scotland streams covering a range of land use-related pollution pressures. Pollution explanatory variables were as assessed from GIS-derived land cover areas, dissolved water chemistry (N, P, base cations and trace elements) and sediment trace metals (by aqua-regia digest). Large inter-site variation in dissolved and sediment chemical concentrations was strongly significantly correlated with land cover: dissolved N, Ca, Mg, K, Na positively with agriculture and urban, negatively with semi-natural land areas; sediment As, Ba, Co, Zn with agriculture, Cu, Pb, Zn with urban areas. Simple linear regression modelling was used to explore the influences across land cover, dissolved and sediment chemistry with C-substrate responses, both individually and using principal components-derived SIR 'fingerprints'. The data supported the hypothesis that pollution pressures altered water and sediment quality, in turn affecting sediment microbes and their respiration responses to a range of C-substrates, especially discriminating the DOM respiration. Since headwater DOM is a dominant pool of C driving ecosystem processes downstream then any loss of ability to utilise DOM should be further explored in terms of possible connections to pollution processes. Graphical abstract: Highlights: Microbial C cycling can impact river pollution processing. Respiration responses of C-substrates is an indicator of aquatic microbial condition. Pollution pressures affected water, sediment quality and C-substrate respiration. River organic matter drives ecosystem processes but seems impacted by pollution.